Benefits and Challenges in BPM Adoption in Organizations: An Analysis of Industry Professionals’ Perceptions - Rodrigues, Felipe; Vilela, Jéssyka; Alves, Carina (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2026: Anais do XXII Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2026.248288, 2026)
Research Context: Business Process Management (BPM) is as a key strategic approach to enhance organizational efficiency and align operations with digital transformation. In the face of constant technological evolution and market demands, organizations are challenged to integrate BPM within increasingly dynamic environments, where people, processes, and technologies must operate in synergy. Scientific and/or Practical Problem: It is crucial to understand how BPM is currently perceived, implemented, and evaluated in organizations, considering both the consolidated theoretical foundations of recent decades and the new practices that are emerging in organizational contexts. Proposed Solution and/or Analysis: This study investigates the critical success factors, main challenges, and perceived benefits of BPM adoption, based on the perspectives of professionals from both public and private organizations. The focus is on the organizational domain and the interplay between people, processes, and technologies. Related IS Theory: The research is grounded in the Socio-technical Systems Theory, which views organizations as interdependent systems composed of social and technical subsystems. This theory supports the analysis of how BPM effectiveness depends on the balanced integration of human, technological, and organizational elements. Research Method: A survey was conducted with 62 professionals using a structured questionnaire based on existing literature and adapted from a previous study to capture updated perceptions about BPM practices. Summary of Results: Findings show that while BPM is recognized for its strategic value (especially in improving communication, standardization, and organizational alignment)it still faces obstacles such as low maturity, cultural resistance, and lack of performance indicators. Leadership support, team training, and cross-level engagement are highlighted as key enablers of BPM success. Contributions and Impact to IS area: This study contributes to Information Systems research by emphasizing BPM as a socio-technical approach and offering theoretical and practical insights into its implementation in organizational settings undergoing digital transformation.